Use of antibodies to carcinoembryonic antigen and human milk fat globule to distinguish carcinoma, mesothelioma, and reactive mesothelium. - Robert J. Marshall; Amanda Herbert; Stephen Braye; David Jones (1984)
Antibodies raised against human milk fat globule (HMFG 1 and 2) and carcinoembryonic antigen were used in an immunoperoxidase technique to differentiate mesothelioma, carcinoma, and benign, reactive mesothelium. Sixteen mesotheliomas, 27 lung carcinomas, and 13 specimens of reactive mesothelium were examined. Staining for carcinoembryonic antigen was not seen in reactive mesothelium or mesothelioma but was present in 22 of 27 carcinomas. Mesothelioma and carcinoma usually stained with HMFG 1 and 2; reactive mesothelium did not. These three antibodies may help to distinguish carcinoma, mesothelioma, and reactive mesothelium.